Simple Experimental Methods for Early Childhood Cognitive Development: Metode Eksperimen Sederhana untuk Perkembangan Kognitif Anak Usia Dini - Nilawarti; Fitriah; Anwar, Kaspul; Wati, Evi Sulistia; Mardiana (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Cognitive development in early childhood is a fundamental domain that shapes logical reasoning, problem-solving skills, and observational abilities. Specific Background: However, learning activities in early childhood education often remain dominated by rote memorization with limited exploratory engagement. Knowledge Gap: Few studies have systematically applied simple experimental methods as a structured learning strategy in early childhood settings. Aims: This study investigates the application of simple experiments to optimize the cognitive development of children aged 5–6 years in TK Marwah, Tanjung Jabung Timur. Results: Using a classroom action research design with two cycles and 12 children as participants, data were collected through observation, interviews, and documentation. Findings indicate significant improvements in children’s abilities to observe, classify, and conclude, with cognitive achievement increasing from 41.6% in the pre-cycle to 83.3% in the second cycle. Novelty: The study highlights how simple, playful scientific activities—such as color mixing and observing changes in objects—provide meaningful stimulation for early cognitive growth. Implications: These results suggest that simple experimental methods can be integrated into early childhood curricula to foster scientific thinking and active learning. Highlights: Structured simple experiments stimulate scientific thinking in early learners. Cognitive achievement improved significantly across two research cycles. Practical approach applicable for sustainable early childhood education. Keywords: Simple Experiment, Cognitive Development, Early Childhood, Scientific Learning, Active Learning